2019
DOI: 10.3390/foods8010030
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Water Activity and Moisture Content in Floral Honey

Abstract: The water activity (Aw) and moisture content (MC) data of floral honey at five temperatures were determined using the Aw method and it was found that temperature significantly affected the Aw/MC data. The linear equation could be used to express the relationship between Aw and MC of honeys. The empirical regression equations between parameters and temperature were established. To evaluate the factors affecting the Aw/MC data, we used categorical tests of regression analysis to assess the effect of the correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 18 publications
1
21
0
2
Order By: Relevance
“…The low moisture contents of the samples largely translate to low water activity [17]. These lower moisture values suggest more stability and longer storability as little or no free moisture might be available for microbial activity [18].…”
Section: Resultsmentioning
confidence: 99%
“…The low moisture contents of the samples largely translate to low water activity [17]. These lower moisture values suggest more stability and longer storability as little or no free moisture might be available for microbial activity [18].…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al (2015) reported that the drying rate increased in the dehydration of kiwi slices with high free moisture content. Besides, the water activity observed for T3 (0.58) and T6 (0.53) were below 0.6 (Table 2), indicating that they will have extended shelf-life, even without refrigeration, or save for the growth of pathogens including osmotolerant yeasts (Chen, 2019).…”
Section: Moisture and Water Activity Measurementmentioning
confidence: 99%
“…There was a correlation between water activity and moisture content. The higher the moisture content, the higher the water activity [23].…”
Section: Fig 2 Water Activity Of Shredded Catfish Added With Differementioning
confidence: 99%